The Effect Of Exchange Rate Movements On Trade Balance: A Chronological Theoretical Review - Dhakir Abbas Ali; Fuadah Johari; Mohammad Haji Alias (Hindawi Publishing Corporation, 2024)
Volume: 2014 (page: 1-6)